2020
DOI: 10.4081/jphr.2020.1870
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mid Sleep Time and Social Jetlag with Psychosocial Behaviour of Indian Population during Covid-19 Lockdown

Abstract: Background: India, being the third worst affected country from COVID-19 pandemic at the time of study, faced complete lockdown to minimize community transmission that confined people to social isolation for extended durations. Design and Methods: Therefore, we conducted an online questionnaire-based survey for the Indian population after 37 days of complete lockdown to assess the integrative effects of such home restriction and social isolation on mid-sleep time, social jetlag, and their associated psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Sixty-one studies used self-reported instruments ( 30 76 , 79 92 ) and 2 device-based (DB) ones ( 77 , 78 ). Of the former, 20 used validated instruments ( 32 , 33 , 42 , 43 , 47 , 51 , 54 , 61 , 63 , 65 , 66 , 68 , 69 , 71 73 , 84 , 85 , 88 , 90 ) (17 PSQI), and 41 used researcher-developed ones ( 31 , 34 41 , 44 46 , 48 50 , 52 , 53 , 55 60 , 62 , 64 , 67 , 70 , 74 76 , 79 83 , 86 , 87 , 89 , 91 , 92 ). With regard to the researcher-developed instruments, some studies utilized selected items of validated tools, but in the majority of cases the investigators asked the participants to evaluate if they had noted a change (either an improvement, worsening or no change) in the sleep outcome being examined during the lockdown with respect to pre-lockdown status.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-one studies used self-reported instruments ( 30 76 , 79 92 ) and 2 device-based (DB) ones ( 77 , 78 ). Of the former, 20 used validated instruments ( 32 , 33 , 42 , 43 , 47 , 51 , 54 , 61 , 63 , 65 , 66 , 68 , 69 , 71 73 , 84 , 85 , 88 , 90 ) (17 PSQI), and 41 used researcher-developed ones ( 31 , 34 41 , 44 46 , 48 50 , 52 , 53 , 55 60 , 62 , 64 , 67 , 70 , 74 76 , 79 83 , 86 , 87 , 89 , 91 , 92 ). With regard to the researcher-developed instruments, some studies utilized selected items of validated tools, but in the majority of cases the investigators asked the participants to evaluate if they had noted a change (either an improvement, worsening or no change) in the sleep outcome being examined during the lockdown with respect to pre-lockdown status.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the researcher-developed instruments, some studies utilized selected items of validated tools, but in the majority of cases the investigators asked the participants to evaluate if they had noted a change (either an improvement, worsening or no change) in the sleep outcome being examined during the lockdown with respect to pre-lockdown status. Forty-eight of the studies were cross-sectional ( 30 , 31 , 33 50 , 52 , 53 , 57 , 58 , 60 64 , 66 , 67 , 69 71 , 73 75 , 79 83 , 86 90 , 92 ) and 15 were longitudinal ( 32 , 51 , 54 56 , 59 , 65 , 68 , 72 , 76 78 , 84 , 85 , 91 ). The mean NOS score for the cross-sectional studies was 4.1 (SD = 1.3; range 1-7); it was 5.1 (SD = 1.0; range 3-8) for the longitudinal studies (see Supplementary Table 2 for full scoring information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to quality-type measures, many researchers examined changes in sleep patterns during the COVID-19 quarantines. Delays in sleep timing which frequently included a concomitant increase in sleep quantity were commonly found across many countries ( Benham, 2020 ; Blume et al, 2020 ; Sinha et al, 2020 ; Wright et al, 2020 ; Cellini et al, 2021 ; Conte et al, 2021 ; Robillard et al, 2021 ; Tahara et al, 2021 ). The delays in sleep timing included later bedtimes, mid-sleep times, and wake-up times often resulting in less social jetlag (where sleep times differ between workdays and non-workdays).…”
Section: Social Isolation and Sleep During Covid-19mentioning
confidence: 99%
“…According to a study on school teachers, yoga practice has been actively pursued to effectively reduce anxiety and stress, so that improved sleep can positively impact immunity. As a result, there is a surge in social media contributing to regular online Yoga classes, which seem to be bene icial in offering convenient means to achieve both mental and physical well-being (Sinha et al, 2020a). Among the adult population of Maharashtra, 33% of people might have adopted these strategies to cope up with the psychological stress associated with lockdown, according to this survey.…”
Section: Resultsmentioning
confidence: 96%